The Usage of Fly Ash for Reclaimed Asphalt Pavement (RAP), Asphalt Concrete Binder Course (AC-BC) Filler - Ratna Handayani; Ria Asih Aryani Soemitro; Herry Budianto; Januarti Jaya Ekaputri (IPTEK Journal of Proceedings Series, 2017)
Material Reclaimed Asphalt Pavement (RAP) and fly ash as waste that whose is abundant. So interesting to be researched. The research will be started by analyze of RAP, be obtained  characteristics of aggregates and asphalt, then analyzed on an aggregate  gradation; if aggregate gradation does not on gradation envelope will be required the addition of new aggregate. If asphalt  does not  match the requirements then also be required  the addition of new asphalt.  The next will be made the composition of mix- design  for  Asphalt Concrete - Binder Course (AC-BC) with variations addition of fly ash volume as filler. The aim of research to get variations addition of fly ash volume (4%,5% and 6%)